2022
DOI: 10.1155/2022/1155989
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Balance between Protein, Lipid and Carbohydrate in Diets for Lumpfish (Cyclopterus lumpus)

Abstract: The aim of this study was to investigate how the dietary balance between protein, lipid, and carbohydrate affects growth, welfare, and health with focus on immune responses, in lumpfish of body weight ranges 1.7-10 g and 15-50 g. A three-component mixture design, with simultaneous variation of the three macronutrients was applied. Growth, tissue and plasma nutrient composition, welfare, cataract frequency, and immune responses in leukocytes isolated from the fish head kidney were studied. Most responses were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…As mentioned in the introduction, our previously published results from E1, indicated that peak performance of lumpfish weighing between 15 and 50g, based on growth, body composition, welfare score and immune responses in isolated head kidney cells, would be obtained with a diet containing 55% protein, minimum 17% lipid and maximum 6% carbohydrate (Hamre et al, 2022). The present results, showing very low starch digestibility, suggest that dietary starch level should be limited to about 6%.…”
Section: Indication Of Optimum Balance Between the Dietary Macronutri...supporting
confidence: 59%
See 3 more Smart Citations
“…As mentioned in the introduction, our previously published results from E1, indicated that peak performance of lumpfish weighing between 15 and 50g, based on growth, body composition, welfare score and immune responses in isolated head kidney cells, would be obtained with a diet containing 55% protein, minimum 17% lipid and maximum 6% carbohydrate (Hamre et al, 2022). The present results, showing very low starch digestibility, suggest that dietary starch level should be limited to about 6%.…”
Section: Indication Of Optimum Balance Between the Dietary Macronutri...supporting
confidence: 59%
“…Details of the experimental conditions are published in (Hamre et al, 2022). In brief, the fish were produced by a commercial hatchery and transported to Nofima's research facility at Sunndalsøra, Norway.…”
Section: Fish and Feed For Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is defined as protein-sparing effect of lipid, which is beneficial to reduce feed cost and nitrogenous waste output in fish farming [4]. In recent years, some research findings have evidenced that diets with appropriate protein and lipid levels are performing well in terms of fish growth and feed utilization, while a sparing effect on protein by increased dietary lipid has also been found in several fish [5][6][7]. However, most commercial feeds containing relatively high level of protein and lipid are applied in offshore cage farming, resulting in feed waste, and potential environmental pollution.…”
Section: Introductionmentioning
confidence: 99%